Detection of P. aeruginosa harboring bla(CTX-M-2), bla(GES-1) and bla(GES-5), bla(IMP-1) and bla(SPM-1) causing infections in Brazilian tertiary-care hospital - Polotto, Milena [UNESP]; Casella, Tiago [UNESP]; de Lucca Oliveira, Maria Gabriela; Rubio, Fernando G.; Nogueira, Mauricio L.; de Almeida, Margarete T. G.; Nogueira, Mara C. L. (Biomed Central Ltd., 2012)
Background: Nosocomial infections caused by Pseudomonas aeruginosa presenting resistance to beta-lactam drugs are one of the most challenging targets for antimicrobial therapy, leading to substantial increase in mortality rates in hospitals worldwide. In this context, P. aeruginosa harboring acquired mechanisms of resistance, such as production of metallo-beta-lactamase (MBLs) and extended-spectrum beta-lactamases (ESBLs) have the highest clinical impact. Hence, this study was designed to investigate the presence of genes codifying for MBLs and ESBLs among carbapenem resistant P. aeruginosa isolated in a Brazilian 720-bed teaching tertiary care hospital.Methods: Fifty-six carbapenem-resistant P. aeruginosa strains were evaluated for the presence of MBL and ESBL genes. Strains presenting MBL and/or ESBL genes were submitted to pulsed-field gel electrophoresis for genetic similarity evaluation.Results: Despite the carbapenem resistance, genes for MBLs (bla(SPM-1) or bla(IMP-1)) were detected in only 26.7% of isolates. Genes encoding ESBLs were detected in 23.2% of isolates. The bla(CTX-M-2) was the most prevalent ESBL gene (19.6%), followed by bla(GES-1) and bla(GES-5) detected in one isolate each. In all isolates presenting MBL phenotype by double-disc synergy test (DDST), the bla(SPM-1) or bla(IMP-1) genes were detected. In addition, bla(IMP-1) was also detected in three isolates which did not display any MBL phenotype. These isolates also presented the bla(CTX-M-2) gene. The co-existence of bla(CTX-M-2) with bla(IMP-1) is presently reported for the first time, as like as co-existence of bla(GES-1) with bla(IMP-1).Conclusions: In this study MBLs production was not the major mechanism of resistance to carbapenems, suggesting the occurrence of multidrug efflux pumps, reduction in porin channels and production of other beta-lactamases. The detection of bla(CTX-M-2), bla(GES-1) and bla(GES-5) reflects the recent emergence of ESBLs among antimicrobial resistant P. aeruginosa and the extraordinary ability presented by this pathogen to acquire multiple resistance mechanisms. These findings raise the concern about the future of antimicrobial therapy and the capability of clinical laboratories to detect resistant strains, since simultaneous production of MBLs and ESBLs is known to promote further complexity in phenotypic detection. Occurrence of intra-hospital clonal dissemination enhances the necessity of better observance of infection control practices.
Keywords: P. aeruginosa; Nosocomial infection; ESBL; MBL; CTX-M-2; GES-1; GES-5; IMP-1; SPM-1